2001
DOI: 10.1021/la010306z
|View full text |Cite
|
Sign up to set email alerts
|

Ostwald Ripening of Alkane Emulsions Stabilized by Polyethylene Glycol Monolaurate

Abstract: The Ostwald ripening of alkane in water emulsions stabilized by the surfactant poly(ethylene glycol) monolaurate (PEM) was investigated. Surprisingly the measured ripening rates were significantly below the rate which can be predicted by the Lifshitz−Slyozov−Wagner (LSW) theory and decreased in the presence of surfactant micelles. A possible explanation of the effect of these micelles is that they withdraw oil from the continuous phase and hence slow the transport of oil from smaller to larger droplets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
4
14
3
Order By: Relevance
“…It is shown that the slope declines with the decreasing R os , which means the more stable nanoemulsions are obtained with higher surfactant concentration. This phenomenon is consistent with results reported earlier [35][36][37]. It was suggested that excess micelles formed in the aqueous phase, which act a solubilization sites for added oil.…”
Section: Stability Of Nanoemulsionssupporting
confidence: 93%
“…It is shown that the slope declines with the decreasing R os , which means the more stable nanoemulsions are obtained with higher surfactant concentration. This phenomenon is consistent with results reported earlier [35][36][37]. It was suggested that excess micelles formed in the aqueous phase, which act a solubilization sites for added oil.…”
Section: Stability Of Nanoemulsionssupporting
confidence: 93%
“…This treatment will yield the Ostwald ripening rate in the presence of micelles, predicting a remarkable increase of the rates [18,19]. However, Smet et al [27] and Hoang et al [28] observed a reduced ripening rate with increasing surfactant concentration. They argued that the oil solubilized in the micelles was not dispersed at the molecular level in the continuous phase.…”
Section: Long Term Stabilitymentioning
confidence: 96%
“…The equilibrium solubility of oil in micelles, c eq mic , is several orders of magnitude higher than the molecular solubility c eq w of the oil. Yet the enhancement in experimentally measured Ostwald ripening rates, x E , in the presence of micelles, relative to that in their absence, is found to be much weaker than expected based on this solubility increase [7][8][9][10][11][12][13]. Furthermore, studies of systems containing ionic surfactants found that x E was virtually independent of surfactant concentration, leading researchers to conclude that there is no contribution from anionic micelles to the ripening mechanism [7,9,10].…”
Section: Introductionmentioning
confidence: 99%